2016
DOI: 10.1016/j.yjmcc.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolemmal Ca 2+ -entry through L-type Ca 2+ channels controls the profile of Ca 2+ -activated Cl − current in canine ventricular myocytes

Abstract: Highlights• Ca 2+ -entry via I Ca,L is essential for the activation of I Cl(Ca) • I Cl(Ca) can be activated even in the absence of CICR• TMEM16A and Bestrophin-3 are expressed on human left ventricular muscle• TMEM16A and Bestrophin-3 co-localize with each other and with Ca v 1.2 channels (I Cl(Ca) ) mediated by TMEM16A and/or Bestrophin-3 may contribute to cardiac arrhythmias. The true profile of I Cl(Ca) during an actual ventricular action potential (AP), however, is poorly understood. We aimed to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 65 publications
3
20
0
Order By: Relevance
“…I Cl(Ca) started to activate at −20 mV and had its highest value at +60 mV in all studied cell types (Fig. 3B, C) similarly to our earlier studies [28,31]. …”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…I Cl(Ca) started to activate at −20 mV and had its highest value at +60 mV in all studied cell types (Fig. 3B, C) similarly to our earlier studies [28,31]. …”
Section: Resultssupporting
confidence: 89%
“…Previously we have confirmed the expression of TMEM16A and Bestrophin-3 on both canine and human isolated left ventricular cardiomyocytes [28]. It was also shown that these two proteins co-localize with each other and Ca v 1.2 suggesting a direct control of I Cl(Ca) by Ca 2+ entry through L-type Ca 2+ channels (LTCCs) in canine ventricular myocytes [28]. Although a previous publication found no evidence for the existence of I Cl(Ca) in healthy human ventricular myocytes [29] but this was not confirmed later.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations